Social exclusion: re-examining its conceptual relevance to tackling inequality and social injustice. Issue 9 (8th September 2015) - Sealey, Clive
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to rationalise the continued conceptual utility of social exclusion, and in so doing addresses the prevailing question of what to do with it. This is relevant from social exclusion's declining relevance in contemporary UK social policy and academia, where its consideration as a concept to explain disadvantage is being usurped by other concepts, both old and new. Design/methodology/approach – The paper analyses criticisms of limitations of social exclusion which have typically centred on the operationalisation of the concept, but the author will argue that there are distinctive operationalisation and conceptual strengths within social exclusion which make it value-added as a concept to explain disadvantage. Specifically, there will be an analysis of both New Labour's and the present Coalition government's conceptualisation of the term in policy in relation to work. Findings – The analysis highlights the significant difference that a focus on processes rather than outcomes of social exclusion can make to our understanding of inequality and social injustice, and locates this difference within an argument that social exclusion's true applied capabilities for social justice requires a shift to a conceptualisation built on the processes that cause it in the first place. Originality/value – The paper acts as a rejoinder to prevailing theoretical and political thinking of the limited and diminishing value of social exclusion for tackling disadvantage. In particular, the paper shows how social exclusion can be conceptualised to provide a critical approach to tackling inequality and social injustice, and in doing so foregrounds the truly applied capabilities of social exclusion for transforming social justice.